A mixture of organic acids and thymol protects primary chicken intestinal epithelial cells from Clostridium perfringens infection in vitro - Federico Ghiselli; Giulia Giovagnoni; Martina Felici; Benedetta Tugnoli; Andrea Piva; Ester Grilli (Poultry Science, 2022)
ABSTRACT: Necrotic enteritis causes economic losses estimated to be up to 6 billion US dollars per year. Clinical and subclinical infections in poultry are also both correlated with decreased growth and feed efficiency. Moreover, in a context of increased antibiotic resistance, feed additives with enhanced antimicrobial properties are a useful and increasingly needed strategy. In this study, the protective effects of a blend of thymol and organic acids against the effects of Clostridium perfringens type A (CP) on chicken intestinal epithelial cells were investigated and compared to bacitracin, a widely used antibiotic in poultry production. Primary chicken intestinal epithelial cells were challenged with CP for a total time of 3 h to assess the beneficial effect of 2 doses of citric acid, dodecanoic acid, and thymol-containing blend, and compare them with bacitracin. During the challenge, different parameters were recorded, such as transepithelial electrical resistance, cell viability, mRNA expression, and reactive oxygen species production. CP induced inflammation with cytokine production and loss of epithelial barrier integrity. It was also able to induce reactive oxygen species production and increase the caspase expression leading to cellular death. The high dose of the blend acted similarly to bacitracin, preventing the disruptive effects of CP and inducing also an increase in zonula occludens-1 mRNA expression. The low dose only partially prevented the disruptive effects of CP but successfully reduced the associated inflammation. This study shows that the usage of thymol combined with 2 organic acids can protect primary chicken intestinal epithelial cells from CP-induced damages creating a valid candidate to substitute or adjuvate the antibiotic treatment against necrotic enteritis.